Temporal analysis of suicide attempts attended at an emergency hospital in agreste Alagoas, Brazil (Research, Society and Development, 2021)
Objective: To carry out a temporal analysis of suicide attempts in rural Alagoas. Method: Quantitative approach study with descriptive document analysis, carried out in an emergency hospital located in the city of Arapiraca, in the State of Alagoas, Brazil. The data were obtained using the Individual Notification Form for Interpersonal and Self-Harm Violence and the Exogenous Intoxication Notification Form, related to patients treated for suicide attempts in the hospital, between 2009 and 2017. Results: During the study period, a total was identified 4,704 visits for suicide attempts. Women (70.4%) attempted more suicide than men (29.6%) and attempts were more frequent in adolescents and young adults between 15 and 39 years old (75.9%), with low education (23.1 %), self-declared browns (25.9%) and single (16.5%), occurring mainly in the months of October, November (both with 9.6%) and December (10.1%). The most used method was exogenous poisoning (94.6%). There was a significant difference between the means of suicide attempt per month per year (p = 0.000), age group (p = 0.023) and poisoning method (p = 0.000). Conclusion: Between 2009 and 2017 a similar number of cases was found over the years, demonstrating that no preventive measures were implemented by the health service in the municipality. It is necessary to articulate the Psychosocial Care Network to strengthen care in the prevention of suicide, through an intervention carried out by a multidisciplinary team.